Understanding the Shade Tolerance Responses Through Hints From Phytochrome A-Mediated Negative Feedback Regulation in Shade Avoiding Plants - Xu, Huiying; Chen, Peirui; Tao, Yi (Frontiers in Plant Science, 2021)
Based on how plants respond to shade, we typically classify them into two groups: shade avoiding and shade tolerance plants. Under vegetative shade, the shade avoiding species induce a series of shade avoidance responses (SARs) to outgrow their competitors, while the shade tolerance species induce shade tolerance responses (STRs) to increase their survival rates under dense canopy. The molecular mechanism underlying the SARs has been extensively studied using the shade avoiding model plant Arabidopsis thaliana, while little is known about STRs. In Aarabidopsis, there is a PHYA-mediated negative feedback regulation that suppresses exaggerated SARs. Recent studies revealed that in shade tolerance Cardamine hirsute plants, a hyperactive PHYA was responsible for suppressing shade-induced elongation growth. We propose that similar signaling components may be used by shade avoiding and shade tolerance plants, and different phenotypic outputs may result from differential regulation or altered dynamic properties of these signaling components. In this review, we summarized the role of PHYA and its downstream components in shade responses, which may provide insights into understanding how both types of plants respond to shade.